IOS forensic analysis for iPhone, iPad, and iPod Touch - Morrissey, Sean ([Apress], 2010)
"IOS Forensic Analysis provides an in-depth look at investigative processes for the iPhone, iPod Touch, and iPad devices. The methods and procedures outlined in the book can be taken into any courtroom. With iOS information never published before and data sets that are new and evolving, this book gives the examiner and investigator the knowledge to complete a full device examination that will be credible and accepted in the forensic community"--Provided by publisher